CHILDREN SUFFERING FROM CARDIONEUROSIS: SYMPTOMS AND TREATMENT - Kozirakhimova Nargiza Kodirjonovna (Western European Studies, 2024)
This article revisits the important role of preventive strategies against cardioneurosis in children. It analyzes the latest publications on cardioneurological and pediatric interventions and preventive methods, highlighting the challenges and providing recommendations for future research and practical application.
Keywords: Cardioneurosis; cardiovascular system; prevention; psychosomatics